1995
DOI: 10.1111/j.1476-5381.1995.tb14978.x
|View full text |Cite
|
Sign up to set email alerts
|

Polydeoxyribonucleotides and nitric oxide release from guinea‐pig hearts during ischaemia and reperfusion

Abstract: 1 Two polydeoxyribonucleotides, produced by the controlled hydrolysis of DNA of mammalian lung (defibrotide and its lower molecular weight fraction, P.O. 085 DV), were studied for their ability to modify the release of nitrite and the coronary flow in perfusates collected from isolated, normally perfused hearts of guinea-pigs and from hearts subjected to regional ischaemia and reperfusion. 2 In guinea-pig normally perfused hearts, both defibrotide (DFT) and its fraction, P.O. 085 DV, increase the amount of nit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…on May 10, 2018. by guest www.bloodjournal.org From CSA in the absence and presence of Wortmannin. DF was able to inhibit the inflammatory reaction caused by CSA, decreasing the expression of VCAM-1 and the activation of p38MAPK, even when the macropinocytic entrance was inhibited, suggesting that DF may be acting at the membrane level.Other effects ascribed to DF are the increase of the nitric oxide generation, 35 the activation of NOS activity, and the reduction of oxidative stress. 36 A reduction in hepatic nitric oxide levels has been shown to contribute to the development of SOS through the disruption of the sinusoidal integrity and subsequent disturbance of the sinusoides.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…on May 10, 2018. by guest www.bloodjournal.org From CSA in the absence and presence of Wortmannin. DF was able to inhibit the inflammatory reaction caused by CSA, decreasing the expression of VCAM-1 and the activation of p38MAPK, even when the macropinocytic entrance was inhibited, suggesting that DF may be acting at the membrane level.Other effects ascribed to DF are the increase of the nitric oxide generation, 35 the activation of NOS activity, and the reduction of oxidative stress. 36 A reduction in hepatic nitric oxide levels has been shown to contribute to the development of SOS through the disruption of the sinusoidal integrity and subsequent disturbance of the sinusoides.…”
mentioning
confidence: 99%
“…Other effects ascribed to DF are the increase of the nitric oxide generation, 35 the activation of NOS activity, and the reduction of oxidative stress. 36 A reduction in hepatic nitric oxide levels has been shown to contribute to the development of SOS through the disruption of the sinusoidal integrity and subsequent disturbance of the sinusoides.…”
mentioning
confidence: 99%
“…Inhibited formation of cysteinyl leukotrienes in leukocyte-perfused isolated rabbit hearts [23] Decreased NFjB transcriptional activity in multiple myeloma cells and bone marrow stromal cells [66] Antagonized vasoconstriction induced by endothelin-1 in human saphenous vein samples [65] Increased nitric oxide generation in isolated, perfused, guinea pig hearts [50] Improved acetylcholine-induced endothelial vasorelaxation in cholesterol-fed rabbits [68], including in rabbits with atherosclerosis [69] Other effects…”
Section: Effects On Vascular Integrity and Vascular Tonementioning
confidence: 98%
“…This increase in nitrite and coronary flow were significantly reduced by NGmonomethyl-L-arginine, the inhibitor of NO synthase. 6 Another interesting study demonstrated an increase in prostaglandin-I 2 production caused by defibrotide, which can counterbalance impaired NO generation and attenuate hyperreactivity of the coronary vasculature, indicating that prostaglandin-I 2 production takes part in NO generation. 7 The study of Takatsuka and colleagues mentioned in the article that administered eicosapentaenoic acid starting 3 weeks before unrelated donor allogeneic transplant, until 180 days following transplantation, was successful in preventing any cases of TMA.…”
mentioning
confidence: 99%